Potential Utilization of Sesame Seed Coat as Raw Material for Flour Production - Azalia Riyandini Nursalsabila Kusuma Utama; Arita Dewi Nugrahini; Mohammad Affan Fajar Falah (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2023)
Sesame seed coat is a by-product from hulled sesame seed industry which has high nutritional content but still has low economic value because it is only used in animal feeding. The purpose of this study is to explore the potential of sesame seed coat as a raw material for making flour by looking at the protein content, dietary fiber, food safety, and antioxidant potential so it can be recovered and used as a value added product. Temperature and time in drying can be the factor that determines the final quality. This study was conducted to investigate the best experimental design in combination of drying temperature and time to acquire the best water content, protein content and fiber content on flour. Testing for microbial contamination with total yeast and mold count and testing for chemical contamination of heavy metals such as mercury (Hg), cadmium (Cd), and lead (Pb) were also carried out to ensure food safety. Testing for antioxidant activity and ferulic acid content were also carried out to determine the potential of sesame seed coat flour as an antioxidant-rich food. The results of this study showed that the best temperature and drying time for making sesame seed coat flour was 60oC and 6 hours. In that conditions, the water content, protein content, total dietary fiber content, antioxidant activity, and ferulic acid content were 13,3333%, 7,3537%, 21,6947, 5.871,2381 ppm, and 8,749 mg/kg respectfully for each category. In the microbial test, the results showed that the number of molds and yeast was 8 x 103 colonies/g, while for the chemical contamination test, it was 0.04 mg/kg for mercury, 0.67 mg/kg for cadmium, and undetectable amount for lead.